130k views
0 votes
Perform the indicated operation. Be sure the answer is reduced.

Perform the indicated operation. Be sure the answer is reduced.-example-1
User Brad Green
by
5.9k points

2 Answers

4 votes


(m)/(n) . (n)/(p) / (p)/(q) \\ = (m)/(p) / (p)/(q) \\ = (m)/(p) . (q)/(p) \\ = \frac{mq}{ {p}^(2) }

Hope it helps...

Regards;

Leukonov/Olegion.

User Ramunas
by
6.0k points
2 votes

Answer:

The correct answer is first option

mq/p²

Explanation:

It is given that, (m/n) * (n/p) ÷ (p/q)

To find the simplified form of given expression

Let (m/n) * (n/p) ÷ (p/q) can be written as,

(m/n) * (n/p) ÷ (p/q) = (m/n) * (n/p) * (q/p)

= (m * n * q)/(n * p * q)

= (m * q)/(p * p)

= mq/p²

Therefore the correct answer is mq/p²

User Jmdecombe
by
5.9k points